2022
DOI: 10.1186/s40337-022-00712-9
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of underweight people with eating disorders on receiving Imagery Rescripting trauma treatment: a qualitative study of their experiences

Abstract: Background The prognosis for underweight individuals with an eating disorder (ED) and posttraumatic stress disorder (PTSD) is worse than for their peers without these comorbid symptoms. This qualitative study explores the experiences of trauma-focused Imagery Rescripting (ImRs) therapy of underweight inpatients being treated for an ED. Objective To test the feasibility and to improve ImRs by understanding the experiences and perspectives of people… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…During trauma treatment, adverse events did occur in three participants; all participants could continue both anorexia nervosa treatment as well as trauma-focused treatment despite the occurrence of adverse events. With regard to acceptability, participants reported that processing trauma interventions at the same time as receiving intensive eating disorder treatment was supportive and helped them with regaining weight ( 33 ). Next, they reported that being offered an integrated treatment gave them hope ( 33 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…During trauma treatment, adverse events did occur in three participants; all participants could continue both anorexia nervosa treatment as well as trauma-focused treatment despite the occurrence of adverse events. With regard to acceptability, participants reported that processing trauma interventions at the same time as receiving intensive eating disorder treatment was supportive and helped them with regaining weight ( 33 ). Next, they reported that being offered an integrated treatment gave them hope ( 33 ).…”
Section: Resultsmentioning
confidence: 99%
“…With regard to acceptability, participants reported that processing trauma interventions at the same time as receiving intensive eating disorder treatment was supportive and helped them with regaining weight ( 33 ). Next, they reported that being offered an integrated treatment gave them hope ( 33 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation